2017
DOI: 10.2196/diabetes.8156
|View full text |Cite|
|
Sign up to set email alerts
|

A Feasible and Efficacious Mobile-Phone Based Lifestyle Intervention for Filipino Americans with Type 2 Diabetes: Randomized Controlled Trial

Abstract: The CONSORT-EHEALTH checklist is intended for authors of randomized trials evaluating webbased and Internet-based applications/interventions, including mobile interventions, electronic games (incl multiplayer games), social media, certain telehealth applications, and other interactive and/or networked electronic applications. Some of the items (e.g. all subitems under item 5 -description of the intervention) may also be applicable for other study designs.The goal of the CONSORT EHEALTH checklist and guideline … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
94
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(98 citation statements)
references
References 47 publications
2
94
1
1
Order By: Relevance
“…The duration of mobile app interventions varied from 3 to 12 months. Most studies were conducted in American or European countries and only five in Asian countries .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The duration of mobile app interventions varied from 3 to 12 months. Most studies were conducted in American or European countries and only five in Asian countries .…”
Section: Resultsmentioning
confidence: 99%
“…As a novel technology, mobile apps have emerged as a promising tool for diabetes self-management. Accumulating evidence has shown that mobile app interventions can lower hemoglobin A 1c (HbA 1c ) and increase physical activity in patients with type 2 diabetes (7,(9)(10)(11). Yet the association between mobile app interventions and weight loss remains inconclusive (12)(13)(14)(15).…”
Section: Study Importancementioning
confidence: 99%
See 2 more Smart Citations
“…The PilAm Go4Health study [ 47 ], which assessed the same Fit&Trim intervention, but for Filipinos with diagnosed T2D, showed a 2.9% overall weight loss among intervention participants. Participants reported that the cultural tailoring strategies (e.g., using Filipino research staff to facilitate the intervention and mobile technology to track health behaviors) were relevant and acceptable.…”
Section: Discussionmentioning
confidence: 99%